PSAK 109: The Efforts to realize Zakat Governance in Baznas Province of South Sulawesi - Jamaluddin Majid; Ambo Asse; Fatimah Fatimah; Farid Fajrin (Universitas Islam Negeri Alauddin Makassar, 2020)
This study aims to determine the application of PSAK 109 in themanagement of zakat and infaq/sadaqah at BAZNAS South Sulawesi Provincein order to realize good zakat governance. This research is a qualitative research with a descriptive analysis approach, using primary and secondary data. Theresults showed that BAZNAS South Sulawesi Province has not implementedPSAK 109, so that the realization of good zakat governance in BAZNAS SouthSulawesi Province has not been achieved properly. Therefore, it is necessary toincrease understanding of human resources, training on the implementation ofPSAK 109 on zakat accounting which regulates the recognition, measurement,presentation and disclosure of zakat, infaq / sadaqah transactions in order to realize good zakat governance of BAZNAS South Sulawesi.